DETERMINATION OF THE VOID SPACE STRUCTURE OF COMPLEX ROCKS USING THE PETROACOUSTIC STUDIES DATA FROM THE SEMYRENKIVSKA AREA - Vyzhva, S.; Bezrodna, I. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The paper presents the analysis of the studies of core from the Well #11 (Semyrenkivska area of the Dnipro-Donetsk depression). The depth ranges, potentially productive to form the reservoir rocks, were defined using their void space structure investigations. The set of studies of the 219-samples collection, presented by the Lower Carboniferous sandstones, was carried out at the petrophysical laboratory of the Institute of Geology. The proprietary methodology of ultrasonic and capacitive investigations data inversion into the parameters of void space structure to determine the void space structure of samples was used. The quantitative assessment of the amounts of different types of rocks porosity: intergranular (granular), fracture and vugular was carried out using the petrophysical data (velocities of primary and secondary waves, open porosity coefficient and volume density). The secondary porosity was also estimated. Fracture voids were detected in the majority of layers. Samples with high (more than 0.35%) and very high (up to 4.5 in the samples of productive horizon C2b) values of fracture porosity were distinguished. Vugular voids were observed for the majority of samples. The amount of vugular porosity reaches the value of 6.5%. The amount of secondary porosity is about 80% of the total pore volume and has higher values than the intergranular porosity for the 92% of all sample collection. 90 samples which refer to reservoir layers on the basis of the petrophysical studies interpretation and void space evaluation for the collection of Semyrenkivska area sandstone samples were defined. The horizon B-18 (21 sample) was identified as most promising. The presented results of investigations can be used to define the potential of rocks from particular depth ranges and lithologic units.